DEFB1 5'UTR Polymorphisms Modulate the Risk of HIV-1 Infection in Mexican Women - Estrada-Aguirre, J.A.; Osuna-Ramírez, I.; Prado Montes de Oca, E.; Ochoa-Ramirez, L.A.; Ramirez, M.; Magallon-Zazueta, L.G.; Gonzalez-Beltran, M.S.; Cazarez-Salazar, S.G.; Rangel-Villalobos, H.; Velarde-Felix, J.S. (Current HIV Research, 2014)
Immunologic and genetic factors are involved in HIV-1/AIDS pathogenesis. Defensins are key molecules in innate immunity that participate in the control and/or development of infection and disease. Using PCR-RFLPs, we determined the association between HIV-1/AIDS and human β-defensin 1 (DEFB1) 5’UTR -52 G/A (rs1799946), -44 C/G (rs1800972), and -20 G/A (rs11362) polymorphisms in three groups of women from the state of Sinaloa, located in the Northwest region of Mexico: i) healthy blood donors; ii) sex-workers; and iii) HIV-1 patients. The -52GG genotype was more frequent in blood donors than in patients (p= 0.023; Odds Ratio, OR= 0.49; 95% CI= 0.25–0.95), whereas the - 52GA genotype was significantly higher in patients (p= 0.013; OR= 2.03; 95% CI= 1.11−3.79, statistical power SP= 98.8%), as well as the frequencies of -20A allele (p= 0.017; OR= 1.60; 95% CI= 1.06−2.40), -20AA genotype (p= 0.047; OR = 2.02; 95% CI= 0.93−4.33) and the ACA haplotype with respect to healthy blood donors (p= 0.000012; OR= 5.82; 95% CI= 2.33–16.43, SP= 99.89%) and sex-workers (p= 0.019; OR= 2.18; 95% CI= 1.07–4.46). Conversely, the ACG haplotype was higher in healthy blood donors than in patients (p= 0.009; OR= 0.55; 95% CI= 0.34–0.89). In addition, the -44CC genotype was associated with a low plasma viral load (p= 0.015), whereas AGA, AGG and GGA haplotypes were more prevalent in individuals with high CD4 counts (p= 0.004, 0.046, and 0.029, respectively). These findings associate DEFB1 5’UTR polymorphisms with HIV-1/AIDS in Mexican women for the first time.
Keywords: sex-workers